CONSUMERS’ SATISFACTION, TRUST, AND LOYALTY TOWARD THE HIJAB ONLINE SHOPS - Arief Hendarto; Hari Wijayanto; Istiqlaliyah Muflikhati (School of Business, IPB University (SB-IPB), 2021)
The number of hijab users in Indonesia is increasing. This study aims to analyze online hijab shop customers' characteristics, the level of satisfaction, trustworthiness, consumer loyalty, and the influence between the level of satisfaction and trust on consumers' loyalty to who buy the hijab at online stores in Indonesia. Data were collected through a questionnaire with a Likert Sala, made using Google Form and distributed online. The study sample of 153 people was determined using a purposive sampling technique. The collected data were analyzed using Structural Equation Modeling (SEM) - Partial Least Square (PLS). The results of this study indicate that: (1) online hijab shop customers are dominated by students aged 17-25 years; (2) Consumer Satisfaction Index (CSI) of 79%, which means that consumers are satisfied with the e-commerce services used by consumers; (3) online hijab shop customers are satisfied with the services provided by online hijab shops; (4) the level of customer loyalty is 72%, which means that consumers have high enough loyalty so that they are willing to keep shopping at the current online hijab shop and are willing to recommend it to consumers' colleagues or relatives; and (5) customer satisfaction and trust have a significant effect on customer loyalty. From the results of this study, it is recommended that online hijab shop managers provide hijab that suits students and students' needs to use them at school or campus and always maintain customer satisfaction and trust so that they continue to be loyal customers. Keywords: hijab online, IPA, satisfaction index, trust, loyalty index